Oncocytic schneiderian papilloma: a rare sinonasal papilloma removed via endoscopic medial maxillectomy - Faizah AR; Mazita A; Marina MB; Jeevanan J; Isa MR (Penerbit UKM, 2010)
There are three types of papilloma which arises from the Schneiderian membrane namely inverted, fungiform and oncocytic. Oncocytic papilloma is the rarest type and occurs predominantly in the older age group. Clinically, its behaviour is similar to inverted papilloma in having both local recurrence and associated malignancy. We report a rare case of oncocytic papilloma arising from the maxillary sinus, extending into the nasal cavity and nasopharynx, in a 78-year-old lady. Despite the longstanding history there was no evidence of associated malignancy in this lesion. An endoscopic medial maxillectomy was successfully utilized for approach and complete tumour excision. In conclusion, oncocytic papilloma should be considered as a differential diagnosis in patients presenting with unilateral polypoid nasal lesions especially in the elderly. In addition, endoscopic medial maxillectomy can provide an adequate approach for complete tumour removal.